Investigation of intermediate layer for Ag/Si metal-semiconductor contacts - Bahri, Bibi Zulaika (2019)
The intermediate layer is a crucial component in thin film metal contacts. In determining Ohmic characteristics, selection of materials used as metal contact can affect device performance. However, in determine a good electrical conductor, it depends on their physical structure which is formed by movement of free electron, thus affect the electrical properties. Yet, there are challenges in applying metal contact due to amorphous characteristic and in order to improve the quality of films, Nd:YAG laser were used as structural treatment. The thickness of top Ag layer is kept constant with different intermediate layer applied onto substrate.The characterizations were investigated by atomic force microscopy (AFM), four point probe (FPP) measurement and ultraviolet-visible spectroscopy (UV-Vis). The result indicates the RMS roughness was changed with the deposition time. The surface of Pt/Ag becomes rougher as deposition time increases. As deposition time increases, the resistivity shows some decrement. However, the fluctuated of resistivity may due to surface roughness scattering mechanism. The lowest resistivity was 6.29 × 10-3 Ω-cm deposited at 120 s. The calculated band gap was obtained as ~2.1-3.0 eV at different deposition time. The morphology of Au/Ag shows the improvement of laser treatment. RMS roughness was decreased with increment of deposition time. Deposition time by 120 s shows the smoother in small size of grain, which indicated the lowest resistivity with 4.26 × 10-4 Ω-cm. The calculated band gap was obtained as ~2.4-2.9 eV at different deposition time. For Pd/Ag, the treatment may alter the morphology of films. RMS roughness was changed with the deposition time. The surface becomes rougher as deposition time increases. This due to thickness of layer contains a higher concentration, but might crack and retard carrier mobility. The fluctuated of resistivity may due to scattering, which negative charge and potential barrier increase. The lowest resistivity was 4.10 × 10-3 Ω-cm deposited at 100 s. The calculated band gap was obtained as ~2.1-2.7 eV at different deposition time. As a conclusion, Au shows the better intermediate layer and has a good metal contact properties compared to Pt and Pd metal.